Quickly Collect Qualitative Data With a Video Booth! - Epperson, Annie (Qualitative and Quantitative Methods in Libraries, 2017)
Cameras are everywhere in modern times, making it easy to collect data on a topic of interest, particularly on a college campus. This workshop describes the use of a “video booth” to pose a small number of questions to individuals, one at a time, in short, focused interviews. Workshop participants learned about a case in which the method, modeled on the practice of virtual reality television shows in the United States, was piloted in a project examining the role that use of the library as a place on campus has in student success. This case study illustrates the effectiveness of collecting qualitative data on a tightly-defined topic in a short period of time in an academic library setting.